2023
DOI: 10.1021/acs.est.2c02312
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Chemical Evidence of Coastal Water Pollution from the Tijuana River in Sea Spray Aerosol

Abstract: Roughly half of the human population lives near the coast, and coastal water pollution (CWP) is widespread. Coastal waters along Tijuana, Mexico, and Imperial Beach (IB), USA, are frequently polluted by millions of gallons of untreated sewage and stormwater runoff. Entering coastal waters causes over 100 million global annual illnesses, but CWP has the potential to reach many more people on land via transfer in sea spray aerosol (SSA). Using 16S rRNA gene amplicon sequencing, we found sewage-associated bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…These antibiotics exhibit ionic properties in the elevated pH, which is indirectly induced by the eutrophication in the Pearl River. Organic species originating from the ocean can enter the atmosphere via two principal mechanisms: the generation of sea spray aerosols through bubble bursting and wind shear, along with the release of volatile organic compounds from the ocean surface. Studies have illustrated that phytoplankton biomass significantly influences aerosol particles generation through wave breaking in both sea and lake environments, leading to an enrichment of matter at the air–water interface. The aerosolization of phytoplankton cells and fragments occurs across a size spectrum ranging from fine (<2.5 μm) to coarse (2.5–10 μm), with microalgal abundance in the atmosphere varying from 10 –4 to 10 4 cells m –3 . , This work revealed that antibiotics transfer to the atmosphere primarily through aerosolization, controlled by phytoplankton biomass. By linearly plotting the concentrations in aerosol-phase concentrations of antibiotics C air against the biomass, negative correlations between C air and phytoplankton biomass were observed in general (Figures a).…”
Section: Resultsmentioning
confidence: 99%
“…These antibiotics exhibit ionic properties in the elevated pH, which is indirectly induced by the eutrophication in the Pearl River. Organic species originating from the ocean can enter the atmosphere via two principal mechanisms: the generation of sea spray aerosols through bubble bursting and wind shear, along with the release of volatile organic compounds from the ocean surface. Studies have illustrated that phytoplankton biomass significantly influences aerosol particles generation through wave breaking in both sea and lake environments, leading to an enrichment of matter at the air–water interface. The aerosolization of phytoplankton cells and fragments occurs across a size spectrum ranging from fine (<2.5 μm) to coarse (2.5–10 μm), with microalgal abundance in the atmosphere varying from 10 –4 to 10 4 cells m –3 . , This work revealed that antibiotics transfer to the atmosphere primarily through aerosolization, controlled by phytoplankton biomass. By linearly plotting the concentrations in aerosol-phase concentrations of antibiotics C air against the biomass, negative correlations between C air and phytoplankton biomass were observed in general (Figures a).…”
Section: Resultsmentioning
confidence: 99%
“…Cabrillostatin appears to be widely distributed in Pacific Ocean seawater and is likely produced by a planktonic organism. Resolving the structure of 1 adds to our understanding of the composition of dissolved organic matter (DOM) [41, 42] and raises questions about the ecological roles of what appears to be a widespread and biologically active natural product. Interestingly, cabrillospirals were not detected in any of the MassIVE datasets, suggesting that some compounds are site specific and justifying broader SMIRC deployments to gauge the extent of chemical diversity that can be captured.…”
Section: Resultsmentioning
confidence: 99%
“…The ever-increasing discharge of industrial oily wastewater has caused extensive damage to the ecological balance and public health in recent years. Oily wastewaters generally contain complicated compositions, such as oil/water emulsions, oil/water multiphase mixtures, or even highly toxic oily/aqueous-soluble dyes, which pose a greater health risk. Membrane separation technology has been widely used in wastewater purification due to its low consumption, high separation efficiency, and convenient operation features. However, traditional separation membranes have poor antifouling performance, resulting in oil droplets or organic dyes in wastewater being easily adhered to the surface of the separation membrane, further blocking the pores during the separation process.…”
Section: Introductionmentioning
confidence: 99%